Autologous Chondrocyte Implantation "Sandwich" Technique Compared With Autologous Bone Grafting for Deep Osteochondral Lesions in the Knee. Issue 2 (February 2018) - Minas, Tom; Ogura, Takahiro; Headrick, Jeff; Bryant, Tim
Background: Treating symptomatic osteochondral defects is challenging, especially in young adults with deep (>8-10 mm) empty defects after osteochondritis dissecans (OCD) or collapsed condyles secondary to avascular necrosis (AVN). For this population, osteoarthritis (OA) is inevitable if articular congruence is not restored. Purpose: To describe the autologous chondrocyte implantation (ACI) "sandwich" technique with autologous bone grafting (ABG) and compare it with ABG alone for restoration of the osteochondral unit. The midterm to long-term outcomes in patients after the treatment for OCD and AVN will be reported and compared. Study Design: Cohort study; Level of evidence, 3. Methods: The outcomes for a consecutive cohort of 24 patients who underwent combined ABG with the ACI sandwich technique between 2001 and 2013 (ACI sandwich group) was compared with a historical control group of 17 consecutive patients who underwent ABG alone between 1995 and 2002 (ABG group) by a single surgeon for symptomatic deep (>8 mm) osteochondral lesions. Patients who were followed up with a minimum of 2 years were included in this study. The modified Cincinnati Knee Rating System, the Western Ontario and McMaster Universities Osteoarthritis Index, a visual analog scale (VAS), the Short Form–36, and a patient satisfaction survey were used to evaluate clinical outcomes. Survival analysis was performed using the Kaplan-Meier method, with no clinical improvement, graft failure, or conversion to prosthetic arthroplasty as the endpoint (failure). Kellgren-Lawrence (K-L) grading to assess OA progression was also performed. Results: In the ABG group, 13 of 17 patients (76%) were available with a mean follow-up of 15.7 years postoperatively (range, 5-21 years). In the ACI sandwich group, all 24 patients were available with a mean follow-up of 7.8 years postoperatively (range, 2-15 years). No significant differences were observed between the groups in terms of age, sex, side of the operated knee, body mass index, lesion type, lesion size, lesion depth, lesion location, or the need for realignment osteotomy. Eight patients (62%) were considered failures in the ABG group, while 3 patients (13%) were considered failures in the ACI sandwich group. The survival rate was significantly better in the ACI sandwich group than the ABG group (87% vs 54% at 5 years, respectively; P = .0025). All functional scores in patients with retained grafts significantly improved in the ACI sandwich group, whereas only the VAS score showed significant improvement in the ABG group. The patient satisfaction survey showed a very high satisfaction rate in the ACI sandwich group, with over 90% of patients reporting their knees as good or excellent and being satisfied with the procedure. In the ACI sandwich group, K-L grading demonstrated no significant OA progression from preoperatively to a mean 5.1 years postoperatively. Conclusion: Our study showed that the ACI sandwich technique provided excellent and superior survival rates compared to ABG alone and significant improvements over midterm to long-term follow-up. This unique treatment offers native joint preservation for conditions that naturally will progress to OA and eventually require prosthetic arthroplasty.